2002
DOI: 10.1080/0962935021000051566
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐inflammatory cytokines in Turkish children with protein‐energy malnutrition

Abstract: BACKGROUND: Protein-energy malnutrition (PEM) results from food insufficiency as well as from poor social and economic conditions. Development of PEM is due to insufficient nutrition. Children with PEM lose their resistance to infections because of a disordered immune system. It has been reported that the changes occurring in mediators referred to as cytokines in the immune system may be indicators of the disorders associated with PEM. AIMS: To determine the concentrations of pro-inflammatory cytokines in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…These polypeptides are synthesized in response to microorganisms and other antigens, and they mediate and regulate immune and inflammatory reactions. Many studies have described alteration in the expression of different cytokines during malnutrition (Mengheri et al 1992;Doherty et al 1994;Ameho et al 1997;Lofty et al 1998;Malavé et al 1998;Dülger et al 2002;Amesty et al 2003;Rodríguez et al 2005;González-Martínez et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…These polypeptides are synthesized in response to microorganisms and other antigens, and they mediate and regulate immune and inflammatory reactions. Many studies have described alteration in the expression of different cytokines during malnutrition (Mengheri et al 1992;Doherty et al 1994;Ameho et al 1997;Lofty et al 1998;Malavé et al 1998;Dülger et al 2002;Amesty et al 2003;Rodríguez et al 2005;González-Martínez et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Several previous studies have demonstrated endothelial dysfunction in obese children [60][61][62][63]; however, in most of these studies, obesity was classified based on different cut-off values and elevated BMIs were selected, very high values compared with the children from our present study.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of chronic undernutrition and infection further weakens the immune response, leading to altered immune cell populations 6,7 and a generalized increase in inflammatory mediators. 8 Reduction of leukotrienes, which enhance leukocyte accumulation and phagocyte capacity, impairs microbial ingestion and killing. 9 The overall effects might include altered microbial colonization of mucosal surfaces and impaired host response to new pathogens.…”
mentioning
confidence: 99%